GABAergic synapses from the ventral lateral septum to the paraventricular nucleus of hypothalamus modulate anxiety - Liu, Ying-Juan; Wang, Yan; Wu, Jiao-Wen; Zhou, Jie; Song, Bai-Lin; Jiang, Yi; Li, Lai-Fu (Frontiers in Neuroscience, 2024)
Emotional disorders, such as anxiety and depression, represent a major societal problem; however, the underlying neurological mechanism remains unknown. The ventral lateral septum (LSv) is implicated in regulating processes related to mood and motivation. In this study, we found that LSv GABAergic neurons were significantly activated in mice experiencing chronic social defeat stress (CSDS) after exposure to a social stressor. We then controlled LSv GABAergic neuron activity using a chemogenetic approach. The results showed that although manipulation of LSv GABAergic neurons had little effect on anxiety-like behavioral performances, the activation of LSv GABAergic neurons during CSDS worsened social anxiety during a social interaction (SI) test. Moreover, LSv GABAergic neurons showed strong projections to the paraventricular nucleus (PVN) of the hypothalamus, which is a central hub for stress reactions. Remarkably, while activation of GABAergic LSv-PVN projections induced social anxiety under basal conditions, activation of this pathway during CSDS alleviated social anxiety during the SI test. On the other hand, the chemogenetic manipulation of LSv GABAergic neurons or LSv GABA -PVN projections had no significant effect on despair-like behavioral performance in the tail suspension test. Overall, LS GABAergic neurons, particularly the LSv GABAergic-PVN circuit, has a regulatory role in pathological anxiety and is thus a potential therapeutic target for the treatment of emotional disorders.